Linking KfW-financed aid projects and FDI: Global evidence at the sub-national level - Laura Wedemeyer; Lennart Kaplan; Jochen Kluve; Lennart Reiners (University of Göttingen, Department of Economics, 2026)
This study analyzes the empirical link between German bilateral development finance and Foreign Direct Investment (FDI) at the sub-national (ADM2) level. We construct a unique dataset by merging geo-referenced development aid projects - implemented by KfW Development Bank - over more than two decades with FDI project data. The analysis investigates four research hypotheses, and finds that: (i) development finance activity is positively and significantly associated with FDI inflows; (ii) the positive link is similarly pronounced in both hard and soft sectors; as well as (iii) irrespective of recipient countries' income level; and (iv) the positive aid-FDI association appears to be driven by projects with stronger implementation, as measured by higher ex-post evaluation ratings. For these higher-rated projects, KfW aid is significantly more likely to be associated with FDI from Germany and the EU. Our findings suggest that FDI may be an important channel through which development aid simultaneously benefits both recipient - by providing capital and technology - and donor countries, by signaling investment opportunities for its enterprises.
Keywords: F23; F35; O12; O18; 330; Development aid; development finance; FDI